Investigation of the anti-wear characteristics of palm oil methyl ester using a four-ball tribometer test - Maleque, Md. Abdul; Masjuki, H.H. (Elsevier BV, 1997)

(untitled)
The aim of this study was to assess the anti-wear characteristics of palm oil methyl ester (POME) in elastohydrodynamic lubrication of EN31 steel ball bearings. A conventional four-ball wear testing machine with different loads was used at 1500 rev miny1 and a test duration of 1 min at ambient room temperature (approximately 28 8C). Optical microscopy of wear worn surfaces revealed the wear mode of mating surfaces. The results provide an nderstanding of the wear characteristics of ball bearings under POME contaminated lubricants. It was found that POME worked as an additive and improved the anti-wear characteristics. The flash temperature parameter (FTP) of the lubricant after each test was also measured.